Do Elections lead to Informed Public Decisions? - Otto H. Swank; Bauke Visser (Tinbergen Institute, 2003)
Democracies delegate substantial decision power to politicians. Using a model in which an incumbent can design, examine and implement public policies, we show that examination takes place in spite of, rather than thanks to, elections. Elections are needed as a carrot and a stick to motivate politicians, yet politicians who are overly interested in re-election shy away from policy examination. Our analysis sheds light on the distance created in mature democracies between the political process and the production of policy relevant information; on the role played by probing into candidates' past; and on the possibility of crowding out desirable political behaviour by increasing the value of holding office.
Keywords: D72; D78; D83; 330; Democracy; Media; Policy Examination; Multiple Tasks; Information; Elections; Neue politische Ökonomie; Wahl; Theorie